Brevhemligheten - För hemlig ur ett brottsbekämpande perspektiv? - Apelgren,Sandra (2021)
A vast amount of drug sales take place daily via the internet and is distributed through the national postal system, where buyers often receive the items to their mailbox. Considering this, the Swedish Government appointed a new Committee to review the duty of confidentiality in the Postal Services Act (2010:1045) in order to increase opportunities for the law enforcement authorities to prevent this illegal trade. In the final report (SOU 2021:29) the Committee propose, among other things, to give staff in the postal service the legal ability to report suspected illegal activity to law enforcement authorities. Since the entry of the Postal Services Act in 1994, postal workers have been barred from reporting suspicious or even confirmed packages with illegal content. The duty of confidentiality that prevents postal employees from contacting authorities in these cases has been motivated by an interest in protecting the personal integrity of senders and receivers of mail. The purpose of this essay is to describe the constitutional right to confidential communications and examine what trade-offs have been made in the legislative history in regard to personal integrity versus effective law enforcement. This essay also intend to investigate whether the new report changes the balance between the two interests related to the right to confidential communications. The essay reaches the conclusion that the balance between personal integrity and effective law enforcement is changed to some extent through the new proposal that enables postal staff to provide information to law enforcement authorities. However, the conclusion is not entirely self-evident as the inquiry does not report in depth on the balance of interests and assessments that have been made in the matter. Unlike previous investigations that have examined the same issue, this Committee conclude that the proposal is appropriate to introduce. This reversal of viewpoint ultimately makes the balance appear to be changing in favor of a more effective law enforcement.
Keywords: straffrätt; brevhemlighet